1995
DOI: 10.1042/bj3051017
|View full text |Cite
|
Sign up to set email alerts
|

Methional derived from 4-methylthio-2-oxobutanoate is a cellular mediator of apoptosis in BAF3 lymphoid cells

Abstract: 4-Methylthio-2-oxobutanoic acid is the direct precursor of methional, which is a potent inducer of apoptosis in a BAF3 murine lymphoid cell line which is interleukin-3 (IL3)-dependent. Cultures treated for 8 h with methional in the presence of IL3 show extensive DNA double-strand breaks on flow cytometric analysis, increases in DNA fragmentation as measured by the amount of non-sedimentable DNA present in the 30,000 g supernatant of cell lysates and the typical laddering pattern of multiples of 180 bp seen upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 44 publications
(59 reference statements)
2
28
1
1
Order By: Relevance
“…First, the adduct appears within 8 h of treatment with CD437, at a point coincident with the onset of apoptosis; 11 secondly, non-apoptotic retinoids RA and CD666 do not cause formation of this adduct, and finally, all CITs are DNA damage-response genes and ei24 is a critical mediator of apoptosis. Although alternative mechanisms cannot be completely ruled out, 40 we believe that our data can be most readily explained by this interpretation. The DNA damage-sensing mechanism in S91 cells then triggers induction of CITs which has dramatic effects on cell physiology.…”
Section: Discussionmentioning
confidence: 78%
“…First, the adduct appears within 8 h of treatment with CD437, at a point coincident with the onset of apoptosis; 11 secondly, non-apoptotic retinoids RA and CD666 do not cause formation of this adduct, and finally, all CITs are DNA damage-response genes and ei24 is a critical mediator of apoptosis. Although alternative mechanisms cannot be completely ruled out, 40 we believe that our data can be most readily explained by this interpretation. The DNA damage-sensing mechanism in S91 cells then triggers induction of CITs which has dramatic effects on cell physiology.…”
Section: Discussionmentioning
confidence: 78%
“…Our studies cannot determine whether MTOB is a direct regulator of ODC or whether some metabolite of MTOB is involved. Studies using BAF 3 murine lymphoid cells have demonstrated that MTOB can be converted to malondialdehyde and methional in cell extracts (45). Interestingly, MTOB and methional at high concentrations can induce apoptosis in BAF 3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[11]. MTOB является непосредственным предшествен-ником метионина в реутилизационном пути и может превращаться в метионал -индуктор апоптоза [12]. Совместно с метилтрансферазой SAM участвует в ре-акции образования карнитина из ГАМК [11].…”
Section: клиническая онкогематологияunclassified